Surface plasmon resonance sensing in gaseous media with optical fiber gratings - Álvaro, GonzÁlez Vila; Ioannou, Andreas; Loyez, Médéric; Debliquy, Marc; Lahem, Driss; Caucheteur, Christophe (My University, 2018)
Surface plasmon resonance excitation with optical fiber gratings has been typically studied in aqueous solutions. This work describes the procedure to excite a plasmon wave in gaseous media and perform refractive index measurements in these environments. Grating photo-inscription with 193 nm excimer laser radiation allows us to obtain slightly tilted fiber Bragg gratings exhibiting a cladding mode resonance comb along several hundreds of nanometers. Their refractive index sensitive range extends from gases to liquids, so operation in both media is compared. We demonstrate that the thickness of the metal coating required for surface plasmon excitation in gases is roughly one third of the one usually used for liquids. The developed platforms exhibit a temperature insensitive response of 78 nm/RIU when tested with different gases.
Keywords: Excimer lasers; Fiber bragg gratings; Optical fibers; Refractive index; Surface plasmon resonance; Optical fiber gratings